Stereotactic Radiosurgery With Concurrent Immunotherapy in Melanoma Brain Metastases Is Feasible and Effective - Liermann, Jakob; Winkler, Julia K.; Syed, Mustafa; Neuberger, Ulf; Reuss, David; Harrabi, Semi; Naumann, Patrick; Ristau, Jonas; Weykamp, Fabian; El Shafie, Rami A.; König, Laila; Debus, Jürgen; et al. (Frontiers in Oncology, 2020)
Objective Stereotactic radiosurgery (SRS) is an established treatment for brain metastases in the management of metastasized melanoma. The increasing use of checkpoint inhibitors in melanoma therapy leads to combined treatment schemes consisting of immunotherapy and SRS that need to be evaluated regarding safety and feasibility. Methods We retrospectively analyzed 36 patients suffering from cerebral metastasized melanoma. Between November 2011 and May 2016, altogether 66 brain metastases were treated with single-fraction SRS (18-20 Gy prescribed to the 80% isodose) in combination with a checkpoint inhibitor (ipilimumab: 82%, pembrolizumab: 14% or nivolumab: 4%), administered within 3 months before or after SRS. Toxicity was evaluated with focus on the incidence of central nervous system (CNS) radiation necrosis (CRN). Overall survival (OS), freedom from local progression (FFLP), freedom from CNS radiation necrosis (FFCRN) and freedom from distant intracranial progression (FFDIP) were analyzed using the Kaplan-Meier method. Results The median follow-up was 25 months (range: 2-115 months). Two patients (6%) presented with cerebral edema CTCAE °III and another two patients (6%) presented with one-sided muscle weakness CTCAE °III after SRS. One of these four symptomatic cases correlated with an observed CRN, the other three symptomatic cases were related to local tumor progression (n=2) or related to the performance of additional whole brain radiotherapy (WBRT). No further CTCAE °III or °IV toxicity was seen. During follow-up, seven of the growing contrast-enhanced lesions were resected, revealing two cases of CRN and five cases of local tumor progression. Altogether, the observed CRN rate of the irradiated metastases was 6-17% at the time of analysis, ranging due to the radiologically challenging differentiation between CRN and local tumor progression. The observed ranges of the one- and two-year FFLP rates were 82%-85% and 73%-80%, respectively. The median FFDIP was 6.1 months, the median OS was 22.2 months. Conclusion In the presented cohort, the combination of SRS and checkpoint inhibitors in the management of cerebral metastasized melanoma was safe and effective. Compared to historic data on SRS only, the observed CRN rate was acceptable. To gain resilient data on the incidence of CRN after combined treatment schemes, prospective trials are needed.